2013
DOI: 10.3390/educsci3010030
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs to Fit in? Who Gets to Stand out? Communication Technologies Including Brain-Machine Interfaces Revealed from the Perspectives of Special Education School Teachers Through an Ableism Lens

Abstract: Some new and envisioned technologies such as brain machine interfaces (BMI) that are being developed initially for people with disabilities, but whose use can also be expanded to the general public have the potential to change body ability expectations of disabled and non-disabled people beyond the species-typical. The ways in which this dynamic will impact students with disabilities in the domain of special education is explored. Data was drawn from six special education school teachers from one school in Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Since ability expectations remain within a medical model, this colors the perceptions of students with disabilities: presenting students with disabilities as ''normal'' as possible may convert to a higher quality of life due to social acceptance (Diep and Wolbring 2013).…”
Section: Critique Of the Normal And Pediatric Cochlear Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since ability expectations remain within a medical model, this colors the perceptions of students with disabilities: presenting students with disabilities as ''normal'' as possible may convert to a higher quality of life due to social acceptance (Diep and Wolbring 2013).…”
Section: Critique Of the Normal And Pediatric Cochlear Implantationmentioning
confidence: 99%
“…It is asked whether developing new communication technologies for people with disabilities is more to allow the non-disabled to be more at ease interacting with people with disabilities, so that people with disabilities appear ''normal'' to meet the requirements of society and economic efficiency (Diep and Wolbring 2013). Activists question the capability of hearing parents to make rational decisions for their deaf children, especially when they are ignorant of the lives of deaf people.…”
Section: Experience Of Minorities and Defending Against Extinctionmentioning
confidence: 99%
“…Various articles covered perceived usefulness whereby this was mostly discussed within the framework of whether an invasive or non-invasive BMI version is more useful. One study investigating the perception of special education teachers on BMI [41] found that ease of use was a major concern that special education teachers voiced in regards to their disabled students using a BMI. The same study revealed that special education teachers envisioned that BMI's have the potential of being useful by furthering the independence, social participation and quality of life of the special education student [41] but they also believed that invasiveness decreases the usefulness of BMI's.…”
Section: Uses Of Technology Acceptance Modelsmentioning
confidence: 99%
“…One study investigating the perception of special education teachers on BMI [41] found that ease of use was a major concern that special education teachers voiced in regards to their disabled students using a BMI. The same study revealed that special education teachers envisioned that BMI's have the potential of being useful by furthering the independence, social participation and quality of life of the special education student [41] but they also believed that invasiveness decreases the usefulness of BMI's. However special education teachers also voiced other parameters which one would not list under the two parameters of TAM such as affordability, need for being invisible as they feared that their students would get ostracized if their new device were too visible, reliability of the device and concern related to reaction of peers [41].…”
Section: Uses Of Technology Acceptance Modelsmentioning
confidence: 99%
See 1 more Smart Citation